Glucose Gel in Infants at Risk for Transitional Neonatal Hypoglycemia - Makker, Kartikeya; Alissa, Rana; Dudek, Christopher; Travers, Laura; Smotherman, Carmen; Hudak, Mark L. (American Journal of Perinatology, 2018)
Objective To evaluate whether glucose gel as a supplement to feedings in infants admitted to the newborn nursery at risk for neonatal hypoglycemia (NH) reduces the frequency of transfer to a higher level of care for intravenous dextrose treatment.Study Design We revised our newborn nursery protocol for management of infants at risk for NH to include use of 40% glucose gel (200 mg/kg). Study population included late preterm, small and large for gestational age infants, and infants of diabetic mothers. We compared outcomes before (4/1/14–3/31/15: Year 1) and after (4/1/15–3/31/16: Year 2) initiation of the revised protocol. Our prospective primary outcome was transfer to the neonatal intensive care unit (NICU) for treatment with a continuous infusion of dextrose.Results NICU transfer for management of NH fell from 8.1% in Year 1 (34 of 421 at-risk infants screened) to 3.7% in Year 2 (14 of 383 at-risk infants screened). Rate of exclusive breastfeeding increased from 6% in Year 1 to 19% in Year 2. Hospital charges for the study population decreased from 801,276 USD to 387,688 USD in Year 1 and Year 2, respectively.Conclusion Our study supports the adjunctive use of glucose gel to reduce NICU admissions and total hospitalization expense.
Keywords: glucose gel; hypoglycemia; breastfeeding; transitional hypoglycemia